International Dispute Settlement Of Montara Oil Spill On Timor Sea Pollu-tion - Maulana Pasya, Muhammad Nuha (LEGAL BRIEF, 2024)
The environment is a very important aspect of human life. In its development, the environment is often used by humans as a basis for human life in fulfilling their daily needs. Humans see the environment as one of the resources that can be utilized. Petroleum is a natural resource produced from fossils that were buried millions of years ago. In the process of exploiting petroleum, of course, it cannot be separated from some of the risks that will be faced. The case of the explosion of the oil rig in Montana Australia, owned by the oil company Petroleum Exploration and Production Authority Australia or (PTTEP). The explosion of the oil rig has an impact on pollution of the marine environment in this case related to state borders, for this reason, international legal classification is needed in dealing with the dispute. In framing the journal entitled International Dispute Resolution of the Motara Oil Spill Against Timor Sea Pollution using qualitative research with a constructivist paradigm approach. From this research, it can be concluded that the dispute resolution process between the two parties, namely Indonesia and PTTEP, uses a class action lawsuit and is based on International Law contained in the 1982 United Nations Convention on the Law of the Sea in the form of absolute responsibility for the Austrian government because it is the owner of the sovereign territory on the rig and is also reinforced by the granting of permits to PTTEP